Approximate Cubic ∗-Derivations on Banach ∗-Algebras - Seo Yoon Yang; Abasalt Bodaghi; Kamel Ariffin Mohd Atan (Abstract and Applied Analysis, 2012)
We study the stability of cubic ∗-derivations on Banach ∗-algebras. We also prove the superstability of cubic ∗-derivations on a Banach ∗-algebra A, which is left approximately unital.